2019
DOI: 10.1002/anie.201814570
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electrocatalysis for the Preparation of (Hetero)aryl Chlorides and Vinyl Chloride with 1,2‐Dichloroethane

Abstract: Although the application of 1,2-dichloroethane (DCE) as ac hlorinating reagent in organic synthesis with the concomitant release of vinyl chloride as au seful byproduct is afantastic idea, it still presents atremendous challenge and has not yet been achieved because of the harsh dehydrochlorination conditions and the sluggish C À Hc hlorination process.Here we report ab ifunctional electrocatalysis strategy for the catalytic dehydrochlorination of DCE at the cathode simultaneously with anodic oxidative aromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(57 citation statements)
references
References 59 publications
1
55
0
1
Order By: Relevance
“…Oxidative halogenation using bromide anions as a bromine source has been described as an interesting alternative. 5 Sodium periiodate 6 and lead tetraacetate 7 have been commonly employed as oxidants in the oxidative bromination of alkenes and alkynes. However, these methodologies require stoichiometric amounts of the oxidant component, also resulting in the consequent generation of large amounts of waste.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative halogenation using bromide anions as a bromine source has been described as an interesting alternative. 5 Sodium periiodate 6 and lead tetraacetate 7 have been commonly employed as oxidants in the oxidative bromination of alkenes and alkynes. However, these methodologies require stoichiometric amounts of the oxidant component, also resulting in the consequent generation of large amounts of waste.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of the diouro moiety proceeds via the same mechanism, but the oxidation peak of CF 2 HSO 2 Na was found much lower than that of CF 3 SO 2 Na by a cyclic voltammetry (CV) experiment. 18 In addition, inspired by the pioneering work of Jiao for 1,2-dichloroethane (DCE) dehydrochlorination, 19 we also found that when the model reaction between 1a and 2a was performed under the standard conditions, the reaction mixture clearly became acidic as shown by pH measurement (in ESI †). Hence, we propose that HCl was generated from the dehydrochlorination of DCE.…”
Section: Robustnessmentioning
confidence: 93%
“…The paired electrolysis has attracted significant interest in electroorganic synthesis that simultaneously produces products at both the cathode and anode along with optimizing the energy efficiency of the oxidation and reduction process [58–67] . The electricity on both electrodes is effectively utilized for the desired reactions in the paired electrolysis.…”
Section: Electroorganic Reactions Catalyzed By B12 Complexmentioning
confidence: 99%